Використання адаптивних технологій при викладанні педіатрії бакалаврам зі спеціальності «Лабораторна діагностика» - Пащенко, Ірина Володимирівна; Пащенко, И. В.; Pashchenko, I. V. (Видавництво «Кім», 2016)
Мета дослідження: аналіз ефективності використання адаптивних технологій при вивчені педіатрії студентами – бакалаврами напряму підготовки «лабораторна діагностика». Матеріали та методи. У навчальному процесі використовувались тести різного рівня складності, ситуаційні задачі, відеоматеріали та мультимедійні презентації. Застосовувались методи адаптивної підтримки, проблемного викладання, лінійного програмування і ефективних тестових завдань. Спосіб викладання враховував індивідуальні особливості студентів. Висновки. Використання адаптивних технологій дозволяє визначити стратегію професійного розвитку майбутніх лаборантів через актуалізацію мотивації та самоорганізації. In this article there are given the modern aspects of adaptive technologies application in teaching Pediatrics to bachelors studying on medical faculty with the specialization in "laboratory diagnostics". The adaptive technologies provide the formation of sequence of the course teaching, intellectual analysis of decisions and support in the solution of tasks based on examples. The basic principle of the creative education is cooperation between the teacher and student. In this context special attention is paid to coaching, which is the technology increasing the efficiency of a student or group due to purposeful motivation and disclosure of potential in the problem solution to student. In educational process there were used tests of different level of complexity, situational tasks, video materials and multimedia presentations. Special attention was paid to problems of the usage of laboratory researches for children's age pathology diagnosis and their meaning for the efficiency of treatment evaluation. Also there was used the adaptive support, which is the method when there are chosen the best students and then the problem is solved by a group of students under control of the teacher. It allowed to acquire better knowledge and to create skills and abilities. For learning of the principles of rendering of emergency medical treatment to children there were used situational tasks with creation of the person-centered situations which demanded independent decision-making. The way of teaching on tutorials considered psychological peculiarities of students and provided nuanced approach considering the level of complexity of material. The usage of adaptive technologies will allow to define the strategy of future laboratory assistants professional development through the actualization of motivation and self-organization. Цель исследования: анализ эффективности использования адаптивных технологий при изучении педиатрии студентами – бакалаврами направления подготовки «лабораторная диагностика». Материалы и методы. В учебном процессе использовались тесты разного уровня сложности, ситуационные задачи, видеоматериалы и мультимедийные презентации. Применялись методы адаптивной поддержки, проблемного обучения, линейного программирования и эффективных тестовых заданий. Способ изложения учитывал индивидуальные особенности студентов. Выводы. Использование адаптивных технологий позволяет определить стратегию профессионального развития будущих лаборантов через актуализацию мотивации и самоорганизации.
Использование адаптивных технологий при преподавании педиатрии бакалаврам по специальности «Лабораторная диагностика»
The usage of adaptive technologies in teaching pediatrics to bachelors with the specialization in “Laboratory diagnostics”
Keywords: адаптивні технології; лабораторна діагностика; педіатрія; адаптивые технологии; лабораторная диагностика; педиатрия; adaptive technologies; laboratory diagnostics; pediatrics